At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Explore thousands of questions and answers from a knowledgeable community of experts ready to help you find solutions. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

given: XZ/MZ=YZ/NZ Prove XZ/MZ=XY/MN

Sagot :

Answer:

By trigonometric ratio;

XZ/sin(b) = XY/sin(c) = YZ/sin(a)

MN/sin(c) = NZ/sin(f) = MZ/sin(d)

∴ XZ/MZ = XY/MN × (sin(b)/(sin(d))

XY/MN  = XZ/MZ × (sin(b)/sin(d))

Where (sin(b)/(sin(d)) = V;

(XZ/MZ)/(XY/MN) = (XY/MN × V)/(XZ/MZ × V)

(XZ/MZ)/(XY/MN) = (XY/MN)/(XZ/MZ)

∴ (XZ/MZ)² = (XY/MN)²

∴ XZ/MZ = XY/MN QED

Step-by-step explanation:

Whereby the shapes in the question are triangles ΔXYZ and ΔMNZ, and given that we have;

XZ/MZ = YZ/NZ, and from the attached drawing, we have;

∠XZY = ∠NZM

By trigonometric ratio, we have;

XZ/sin(b) = XY/sin(c) = YZ/sin(a)

∴ XZ = sin(b)×XY/sin(c)

MN/sin(c) = NZ/sin(f) = MZ/sin(d)

MZ = sin(d)×MN/sin(c)

∴ XZ/MZ = sin(b)×XY/sin(c)/(sin(d)×MN/sin(c)) = XY/MN × (sin(b)/(sin(d))

XY = sin(c) × XZ/sin(b), MN = sin(c) × MZ/sin(d)

XY/MN  = sin(c) × XZ/sin(b)/(sin(c) × MZ/sin(d)) = XZ/MZ × (sin(b)/sin(d))

Let 'V' represent (sin(b)/(sin(d)), we have;

XZ/MZ = XY/MN × V...(1)

XY/MN = XZ/MZ × V...(2)

Dividing equation (1) by (2) gives;

(XZ/MZ)/(XY/MN) = (XY/MN × V)/(XZ/MZ × V) = (XY/MN)/(XZ/MZ)

(XZ/MZ)/(XY/MN) = (XY/MN)/(XZ/MZ)

∴ (XZ/MZ)² = (XY/MN)²

∴ XZ/MZ = XY/MN

View image oeerivona
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Your questions are important to us at Westonci.ca. Visit again for expert answers and reliable information.